Early infestations by arthropod pests induce unique changes in plant compositional traits and leaf reflectance. Issue 11 (26th July 2021) - Nansen, Christian; Murdock, Machiko; Purington, Rachel; Marshall, Stuart
Abstract: BACKGROUND: With steadily growing interest in the use of remote‐sensing technologies to detect and diagnose pest infestations in crops, it is important to investigate and characterize possible associations between crop leaf reflectance and unique pest‐induced changes in plant compositional traits. Accordingly, we compiled plant compositional traits from chrysanthemum and gerbera plants in four treatments: non‐infested, or infested with mites, thrips or whiteflies, and we acquired hyperspectral leaf reflectance data from the same plants over time (0–14 days). RESULTS: Plant compositional traits changed significantly in response to arthropod infestations, and individual chrysanthemum and gerbera plants were classified with 78% and 80% accuracy, respectively. Based on leaf reflectance, individual plants from the four treatments were classified with moderate accuracy levels of 76% (gerbera) and 73% (chrysanthemum) but with a clear distinction between non‐infested and infested plants. Accurate and consistent diagnosis of biotic stressors was not achieved. CONCLUSION: To our knowledge, this is the first study in which infestations by multiple economically important arthropod pests are directly compared and associated with leaf reflectance responses and changes in plant compositional traits. It is important to highlight that imposed stress levels were low, period of infestation was short, and hyperspectral remote‐sensing data were acquired at four time points with analyses based on large data sets (3826 leaf reflectance profiles for chrysanthemum and 4041 for gerbera). This study provides novel insight into crop responses to different biotic stressors and into possible associations between plant compositional traits and hyperspectral leaf reflectance data acquired from crop leaves. Abstract : Accurate and reliable use of remote‐sensing data in the detection and diagnosis of biotic stressors in crops hinges on infestation inducing: (i) unique changes in plant compositional traits, and (ii) detectable and unique features in leaf reflectance profiles. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.